Managing risk and reliability of process plants - Tweeddale, Mark (Gulf Professional Pub., 2003)
There is much specialist material written about different elements of managing risks of hazardous industries, such as hazard identification, risk analysis, and risk management. Managing Risk and Reliability of Process Plants provides a systematic and integrated coverage of all these elements in sufficient detail for the reader to be able to pursue more detailed study of particular elements or topics from a good appreciation of the whole field. The reader would use this book to keep up to date with new developments and, if they are new to the job, to learn more about the subject. The text includes a chapter of case studies and worked examples - including examples of risk assessments, which is consistent with the approach taken throughout the book of applying real-life scenarios and approaches. * Provides a source for reasonable understanding across the whole field of risk management and risk assessment. * Focuses on the how, what, and why of risk management using a consistent and well organized writing style interspersed with case studies, examples, exercises, as well as end matter. * Fills a need in the area of risk assessment and risk management in the process and chemical engineering industry as an essential multi-audience reference/resource tool, useful to managers and students.